The sea house : a novel - Gifford, Elisabeth (St. Martin's Press, 2014)
"In 1860, Alexander Ferguson, a newly ordained vicar and amateur evolutionary scientist, takes up his new parish, a poor, isolated patch on the remote Scottish island of Harris. He hopes to uncover the truth behind the legend of the selkies--mermaids or seal people who have been sighted off the north of Scotland for centuries. He has a more personal motive, too; family legend states that Alexander is descended from seal men. As he struggles to be the good pastor he was called to be, his maid Moira faces the terrible eviction of her family by Lord Marstone, whose family owns the island. Their time on the island will irrevocably change the course of both their lives, but the white house on the edge of the dunes keeps its silence long after they are gone. It will be more than a century before the Sea House reluctantly gives up its secrets. Ruth and Michael buy the grand but dilapidated building and begin to turn it into a home for the family they hope to have. Their dreams are marred by a shocking discovery. The tiny bones of a baby are buried beneath the house; the child's fragile legs are fused together--a mermaid child. Who buried the bones? And why? To heal her own demons, Ruth feels she must discover the secrets of her new home--but the answers to her questions may lie in her own traumatic past. The Sea House is a sweeping tale of hope and redemption and a study of how we heal ourselves by discovering our histories"--